Proceedings of the 3rd ACM Workshop on Information Hiding and Multimedia Security 2015
DOI: 10.1145/2756601.2756614
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sensor Pattern Noise for Source Camera Identification

Abstract: The sensor pattern noise (SPN) based source camera identification technique has been well established. The common practice is to subtract a denoised image from the original one to get an estimate of the SPN. Various techniques to improve SPN's reliability have previously been proposed. Identifying the most effective technique is important, for both researchers and forensic investigators in law enforcement agencies. Unfortunately, the results from previous studies have proven to be irreproducible and incomparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Noticeably, in [14] authors showed that the Peak-to-Correlation Energy (PCE) provides a significantly more robust feature compared to normalized correlation. The vast interest in this research field fostered the creation of reference image datasets specifically tailored for the evaluation of source identification [16], allowing a thorough comparison of different methods [17]. Recently, the authors of [18] addressed the problem of reducing the computational complexity of fingerprint matching, both in terms of time and memory, through the use of random projections to compress the fingerprints, at the price of a small reduction in matching accuracy.…”
Section: Digital Video Source Device Identification Based On Sensomentioning
confidence: 99%
“…Noticeably, in [14] authors showed that the Peak-to-Correlation Energy (PCE) provides a significantly more robust feature compared to normalized correlation. The vast interest in this research field fostered the creation of reference image datasets specifically tailored for the evaluation of source identification [16], allowing a thorough comparison of different methods [17]. Recently, the authors of [18] addressed the problem of reducing the computational complexity of fingerprint matching, both in terms of time and memory, through the use of random projections to compress the fingerprints, at the price of a small reduction in matching accuracy.…”
Section: Digital Video Source Device Identification Based On Sensomentioning
confidence: 99%
“…The sensor pattern noise (SPN) based source camera identification technique has been also well established to solve the SCI problem. However, [Liu et al, 2015] did an extensive evaluation among various ways of enhancing the SPN. They identified which enhancing methods offer some insights into the behavior of SPN for SCI and they achieved a roughly 15% error rate.…”
Section: State Of the Artmentioning
confidence: 99%